The Crisis of Human Rights Discourse - Załuski, Wojciech (PRAWO i WIĘŹ, 2025)
Although the “crisis” of human rights discourse has many aspects, it is hard not to get the impression that the most important of them is the incorrect understanding of the philosophical foundations of these rights. The paper presents various hypotheses regarding the nature of this error. The first hypothesis suggests that this crisis simply stems from philosophical indifference to the problem of philosophically grounding human rights – treating them, in a sense, in isolation from other ethical ideas. The second identifies the source of the crisis in the misguided attempt to ground human rights in ethical relativism. The third, which is somewhat connected to the second, suggests that the crisis arises from the attempt to ground human rights in the idea of radical autonomy, which results in placing freedom above all other values; this attempt seems to be, to some extent, inspired by modern gnosticism, which rejects nature as normative. The paper also discusses various strategies for resolving this crisis.